Analisis Batu Pecah sebagai Bahan Lapisan Pondasi Atas pada Konstruksi Perkerasan Elastis (Flexible Pavement) - Wahyu Rafadi; Nurmaidah Nurmaidah (Politeknik Negeri Lhokseumawe, 2025)
In planning Elastic Ossifiying Construction is we will is always confronted with by problem of quality of and elastic ossifying strength with the certain quality, require to be performed a by a inspection / examination to material to became the elastic ossifying component. With the existence of examination, material have to pursuant to from great road-works execution bina marga of no.01/ST/BM/1972. Foundation coat for the particle petrify to break have in proving with the data examination of result of examination research done/conducted from filter usage, objejct test 100, 500 rotation, part of – soft stone shares, resilience to wheater with attempt soundness.